High-level resistance to bictegravir and cabotegravir in subtype A- and D-infected HIV-1 patients failing raltegravir with multiple resistance mutations. (28th August 2021) - Ndashimye, Emmanuel; Li, Yue; Reyes, Paul S; Avino, Mariano; Olabode, Abayomi S; Kityo, Cissy M; Kyeyune, Fred; Nankya, Immaculate; Quiñones-Mateu, Miguel E; Barr, Stephen D; Arts, Eric J
Abstract: Objectives: The second-generation integrase strand transfer inhibitor (INSTI) bictegravir is becoming accessible in low- and middle-income countries (LMICs), and another INSTI, cabotegravir, has recently been approved as a long-acting injectable. Data on bictegravir and cabotegravir susceptibility in raltegravir-experienced HIV-1 subtype A- and D-infected patients carrying drug resistance mutations (DRMs) remain very scarce in LMICs. Patients and methods: HIV-1 integrase (IN)-recombinant viruses from eight patients failing raltegravir-based third-line therapy in Uganda were genotypically and phenotypically tested for susceptibility to bictegravir and cabotegravir. Ability of these viruses to integrate into human genomes was assessed in MT-4 cells. Results: HIV-1 IN-recombinant viruses harbouring single primary mutations (N155H or Y143R/S) or in combination with secondary INSTI mutations (T97A, M50I, L74IM, E157Q, G163R or V151I) were susceptible to both bictegravir and cabotegravir. However, combinations of primary INSTI-resistance mutations such as E138A/G140A/G163R/Q148R or E138K/G140A/S147G/Q148K led to decreased susceptibility to both cabotegravir (fold change in EC50 values from 429 to 1000×) and bictegravir (60 to 100×), exhibiting a high degree of cross-resistance. However, these same IN-recombinant viruses showed impaired integration capacity (14% to 48%) relative to the WT HIV-1 NL4-3 strain in the absence of drug. Conclusions: Though not currently widely accessible in most LMICs, bictegravir and cabotegravir offer a valid alternative to HIV-infected individuals harbouring subtype A and D HIV-1 variants with reduced susceptibility to first-generation INSTIs but previous exposure to raltegravir may reduce efficacy, more so with cabotegravir.